Effect of Dead Volume on the Efficiency and the Cost to Deliver Medications in Cystic Fibrosis with Four Disposable Nebulizers - Sharon L Ho; Allan L Coates (Canadian Respiratory Journal)
OBJECTIVES: To evaluate the factors that affect nebulizer efficiency and to compare the relative cost effectiveness of nebulized medications used in the treatment of cystic fibrosis (CF), delivered by four types of disposable jet nebulizers that are widely used in hospitals.